A randomized phase 2 study of temsirolimus and cetuximab versus temsirolimus alone in recurrent/metastatic, cetuximab‐resistant head and neck cancer: The MAESTRO study. Issue 14 (4th May 2020) - Seiwert, Tanguy Y.; Kochanny, Sara; Wood, Kevin; Worden, Francis P.; Adkins, Douglas; Wade, James L.; Sleckman, Bethany G.; Anderson, Daniel; Brisson, Ryan J.; Karrison, Theodore; Stadler, Walter M.; Vokes, Everett E.
Abstract : Background: Patients with cetuximab‐resistant, recurrent/metastatic head and neck squamous cell carcinoma (HNSCC) have poor outcomes. This study hypothesized that dual blockade of mammalian target of rapamycin and epidermal growth factor receptor (EGFR) would overcome cetuximab resistance on the basis of the role of phosphoinositide 3‐kinase signaling in preclinical models of EGFR resistance. Methods: In this multicenter, randomized clinical study, patients with recurrent/metastatic HNSCC with documented progression on cetuximab (in any line in the recurrent/metastatic setting) received 25 mg of temsirolimus weekly plus cetuximab at 400/250 mg/m 2 weekly (TC) or single‐agent temsirolimus (T). The primary outcome was progression‐free survival (PFS) in the TC arm versus the T arm. Response rates, overall survival, and toxicity were secondary outcomes. Results: Eighty patients were randomized to therapy with TC or T alone. There was no difference for the primary outcome of median PFS (TC arm, 3.5 months; T arm, 3.5 months). The response rate was 12.5% in the TC arm (5 responses, including 1 complete response [2.5%]) and 2.5% in the T arm (1 partial response; P  = .10). Responses were clinically meaningful in the TC arm (range, 3.6‐9.1 months) but not in the T‐alone arm (1.9 months). Fatigue, electrolyte abnormalities, and leukopenia were the most common grade 3 or higher adverse events and occurred in less than 20% of patients in both arms. Conclusions: The study did not meet its primary endpoint of improvement in PFS. However, TC induced responses in cetuximab‐refractory patients with good tolerability. The post hoc observation of activity in patients with acquired resistance (after prior benefit from cetuximab monotherapy) may warrant further investigation. Abstract : In this randomized clinical trial of patients with cetuximab‐refractory, recurrent/metastatic head and neck squamous cell carcinoma, cetuximab and temsirolimus induced durable responses in some patients (including 1 complete response), and this indicates modest clinical activity. However, in an unselected population, temsirolimus and cetuximab do not improve survival, although further investigation of the combination as a salvage option for patients with prior benefit from cetuximab monotherapy may be warranted.